Purification and Properties of β-Galactosidase From A Thermophilic Fungus Rhizmmucor Pusillus IB8. - Alzwany, Khalid; Aziz, Ghazi; Omer, Mohammed (Iraqi Journal of Science, 2024)
An extracellular β-galactosidase from the thermophilic fungus RhizomucorPusillus IB8 has been purified via several steps included precipitation by ammoniumsulphate at 80 % saturation, DEAE- Cellulose Ion exchange chromatography and gel filteration on sepharose CL-6B column. The Final purification folds and the yield of the enzyme were 42.5 and 24.8 % respectively. The purified β-galactosidase has an optimum pH for its activity between 4.5 to 5, while the optimum pH for enzyme stability was between 5 to 5.5. Futhermore, it was found that the optimum temperature for its activity was 60 C°. The purified enzyme retained approximatly 98% of its original activity when incubated at 60 C° for 60 min. However, 25 % of its activity was lost when incubated for 120 min at the same tmperaure. Activation energy for conversion of the substrate ONPG to products was 6.15 Kcal / mol, whereas, for enzyme denaturation it was 99.3 Kcal / mol. The molecular weight of the purified enzyme was 232000 dalton as determined by gel filtration on sepharose CL-6B. Kinetic studies showed that the Michaelis constant (Km) and maximum velocity (Vmax) values for the purified enzyme using ONPG as a substrate were 0.46 mM and 223 μM /min respectively.